THE HOLISTIC INTEGRATION OF MORAL AND SOCIAL VALUES IN MODERN PEDAGOGY: FROM FOUNDATIONAL SOCIOCULTURAL THEORY TO ADVANCED HIGHER EDUCATION STRATEGIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
By combining traditional sociocultural theories with contemporary culturally sensitive methods, this paper examines the methodical development of moral and social values within educational contexts. The study explores how school culture, instructional coaching, and pedagogical mediation act as catalysts for ethical development, drawing on the works of Vygotsky and Kohlberg. While the provided research focuses heavily on early childhood and secondary education, this article extends those principles to the higher education context, proposing advanced methodologies such as ethical case analysis, service-learning, and reflective professional coaching to foster critical consciousness and professional integrity in adult learners.